Position Movement And Speed Control By Stepper Motor With Microcontroller PIC16F877 - Pin Chye, Kang (Universiti Sains Malaysia, 2006)
The usage of the stepper motor in our daily life has been increasing and can be found easily in our daily life. It shows the important and the benefit of precise movement and speed control of stepper motor. In such, this project has been carry out. This Project mainly objective is to develop a digital microcontroller to control the position and speed of the stepper motor. The input of the motor is control by using keypad while the program display by using the LCD screen. The hardware implementation is done by using the belt that couple with the roller to determine the position movement of the stepper motor .The belt is painted by white dot to represent the pointer and the casing will be number accordingly to the number of the keypad to show the accuracy of the position control. Simulation of the circuit had been done by using PSIM with the stepper motor is replace by the equivalent resistance and inductance according to the motor datasheet. The simulation is carries out to determine the correct sequence is generate to the stepper motor so that it can rotate in the right manner. The wrong step sequence will cause the motor rotate in jerky manner. This Project consist of three main parts include PIC microcontroller, Translator Circuit and Motor Driver Circuit. The PIC microcontroller mainly purpose is to receive input from the keypad and develop output for the purpose of generating the pulse and direction control. The pulses which are sent from the PIC controller will use to triggered the transistor that will act as switch to supply the motor require voltage. The translator circuit will responsible to generate the stepping sequence that needed by the motor. Finally, the driver circuit is to handle the current drawn by the motor windings to avoid any overloaded. In Sum, it can proved that the stepper motor can develop a precise position movement and speed control by using PIC16F877 and can be practice in daily life.